Learning What Schooling Left Out: Making an Indigenous Case for Critical Service-Learning and Reconciliatory Pedagogy within Teacher Education - Poitras Pratt, Yvonne; Danyluk, Patricia (Canadian Journal of Education/Revue canadienne de l'éducation, 2017)
As teacher educators, we argue that the colonial history of First Peoples, coupled with alarming educational disparities, warrants a specialized approach to Indigenous service-learning within teacher training that requires a critical examination of positionality by service-learners. Our study examines the service-learning experiences of non-Indigenous pre-service teachers working in Indigenous classrooms over a three-month period through reflections and focus groups. The results underscore the risk that a lack of critical reflection by service-learners could play in widening existing educational gaps, and concludes that a reversal of perspective on the education gap could enact the possibility of reconciliatory pedagogy.